Perlindungan Hukum Terhadap Pekerja Di Indonesia Berdasarkan Undang-Undang Cipta Kerja - M. Bagus Basofi; Irma Fatmawati (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Law Number 11 of 2020 concerning Job Creation in its preparation uses the Omnibus Law method which covers ten policy areas, namely: improving the investment ecosystem and business activities; employment; convenience, protection and empowerment of cooperatives and SMEs; ease of doing business; research and innovation support; land acquisition; economic area; central government investment and acceleration of national strategic projects; implementation of government administration; and imposition of sanctions. Since the beginning of the Omnibus Law